2023
DOI: 10.1039/d2ta08425b
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive detection of ethylene using metal oxide chemiresistors with a Pd–V2O5–TiO2 yolk–shell catalytic overlayer via heterogeneous Wacker oxidation

Abstract: The precise detection of trace concentrations of ethylene, a plant hormone gas, is essential for controlling plant health and status. However, owing to the simple chemical structure and low reactivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Apart from high-protein foods, fruits and vegetables are perishable foods whose condition can also be evaluated by measuring the plant hormone ethylene (C 2 H 4 ). Moon et al developed a C 2 H 4 gas senor by using Pd–V 2 O 5 –TiO 2 , which showed an extremely high sensitivity and selectivity at sub-ppm levels . The above studies open up new possibilities for more accurate and earlier detection in the field of food safety and quality control.…”
Section: Gas Sensing Applications and Challenges For Tio2 Nanostructuresmentioning
confidence: 99%
“…Apart from high-protein foods, fruits and vegetables are perishable foods whose condition can also be evaluated by measuring the plant hormone ethylene (C 2 H 4 ). Moon et al developed a C 2 H 4 gas senor by using Pd–V 2 O 5 –TiO 2 , which showed an extremely high sensitivity and selectivity at sub-ppm levels . The above studies open up new possibilities for more accurate and earlier detection in the field of food safety and quality control.…”
Section: Gas Sensing Applications and Challenges For Tio2 Nanostructuresmentioning
confidence: 99%
“…4b). 70 They used the Pd–V 2 O 5 –TiO 2 yolk–shell overlayer as a heterogeneous Wacker oxidation catalyst, which reforms less reactive ethylene into highly reactive acetaldehyde. This reforming reaction improved the response to ethylene, as acetaldehyde is a well-known reactive species.…”
Section: Chemoresistive Gas Sensors For Food Quality Monitoringmentioning
confidence: 99%
“…In comparison with the widely studied hetero-HNs, , the different nanobuilding blocks in homo-HNs have the same composition, which can effectively avoid the stress among hetero-HNs and increase the structural stability. Meanwhile, the synergy of different nanounits with similar Fermi energy levels can significantly enhance the sensing ability of pure metal oxides .…”
Section: Introductionmentioning
confidence: 99%